(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the current status of knowledge on measles prevention and control among mothers with children under 5 years old in Phung Hiep district, Hau Giang province in 2024. Subjects and methods: Cross-sectional descriptive survey of over 400 mothers participating in the study on knowledge on measles prevention and control. Collected data was cleaned and processed before starting to analyze using Epidata 6.1 and SPSS 26 software. Results: Knowledge about measles prevention and control of the study subjects included: the cause of measles is the virus (49%); the source of transmission is through the respiratory tract (44.5%), through contact with people with measles (22.3%); signs of detecting measles patients are fever (35.3%); not knowing the complications of measles (49.3%); preventing measles by getting vaccinated against measles (69.8%); having access to information about measles prevention and control (85.3%); general knowledge about measles prevention and control is achieved at 47%, general knowledge is not achieved at 53%. Conclusion: The current situation of mothers with children under 5 years old in Phung Hiep district, Hau Giang province with general knowledge on measles prevention and control is 47%, and 53% with no knowledge. Although the rate of general knowledge is not high, it has been improved compared to before.